Four Floor Building Fragility Analysis With Consideration of The Masonry Infilled Wall Contribution - Hapsari, Isyana Ratna (International Journal of Sustainable Building, Infrastructure and Environment (IJOSBIE), 2020)
Brick masonry confined with concrete frame is very common for non engineered or institutional building in developing countries. This typical building often seriously suffer from earthquake hit the region. This study aims to evaluate seismic performance of this type of building by developing fragility functions of the structure. Masonry wall is modelled as diagonal strut within the concrete frame. The masonry constituents and composite properties were determined for the model. The structure was subjected to incremental static lateral loading while pushover analysis was utilized to predict the re-sponse of the structure. As the damage states were defined from the spectral capacity curves, the fragility functions were develop for the structure. Based on this study, the seismic performance of the buildings can be determined rationally based on the resulting capacity curve: the infilled frame structure can resist maximum load of 20,3 Ã— 103 kN and open frame is only able to withstand 15,2 Ã— 103 kN. From the fragility curve, it can be concluded that the probability of the infilled frame to reach a certain damage state is lower than the open frame. The results confirm the beneficial effect of the ma-sonry wall to increase the seismic resistance of the building.